2021
DOI: 10.3389/fnsys.2021.733684
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Body Orientation in Vestibular-Defective Patients Before and After Unilateral Vestibular Loss

Abstract: Introduction: The unilateral vestibular syndrome results in postural, oculomotor, perceptive, and cognitive symptoms. This study was designed to investigate the role of vestibular signals in body orientation representation, which remains poorly considered in vestibular patients.Methods: The subjective straight ahead (SSA) was investigated using a method disentangling translation and rotation components of error. Participants were required to align a rod with their body midline in the horizontal plane. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Comparing stroke patients, with or without spatial neglect, Rousseaux et al [8] showed that, in patients with spatial neglect, body representation alterations involved lesions of the inferior parietal cortex and the middle part of the superior temporal gyrus. It is interesting to note here that these cortical structures are also areas of vestibular projections, which could explain the disturbance of the SSA in patients with vestibular impairment [9][10][11]. Another result of the present study was the involvement of the cerebellum in body representation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Comparing stroke patients, with or without spatial neglect, Rousseaux et al [8] showed that, in patients with spatial neglect, body representation alterations involved lesions of the inferior parietal cortex and the middle part of the superior temporal gyrus. It is interesting to note here that these cortical structures are also areas of vestibular projections, which could explain the disturbance of the SSA in patients with vestibular impairment [9][10][11]. Another result of the present study was the involvement of the cerebellum in body representation.…”
Section: Discussionsupporting
confidence: 58%
“…In stroke patients, in particular in those suffering from spatial neglect, damage of the same right cortical structures proved to be involved in ipsilesional SSA deviation [7, 8]. An ipsilesional SSA deviation has also been observed after unilateral peripheral vestibular injury, in particular after left injury [9‒11]. As they have been shown to be vestibular projection areas, the aforementioned cortical areas could be involved, which remains an open issue.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, individuals with UVH perform with similar spatial accuracy compared with healthy individuals, regardless of presence of dizziness. Intact vestibular function is linked to the ability to represent external space as well as accurate body spatial schema ( 122 124 ). This may explain why individuals with unilateral vestibular loss perform at levels similar to healthy individuals.…”
Section: Vestibular Perception: Spatial Orientation and Verticalitymentioning
confidence: 99%